PROPOSTA DE MÉTODO INTEGRAÇÃO ENTRE AUTOPERCEPÇÃO E PERCEPÇÃO EXTERNA ATRAVÉS DO TESTE DE BELBIN E JANELA DE JOHARI: UM ESTUDO DE CASO DO SETOR DE ENERGIA - Santos, Humberto de Faria (2014)
Organizations employ various methods to develop their business and thus achieve better results in business. One of the frequently used methods is related to the enhancement of self-knowledge of the executives. In the organizational context this self-knowledge has to do mainly with the abilities and limitations related to work. One of the methods applied in organizations to help enhance its results uses Belbin Test, the methodology of such test requires its application not only in executives but also in their peers, thus seeking to gain the insight of others in the self-knowledge increase process (Belbin, 2004). The importance of perception of others in self-knowledge process was also tackled by two other scholars, Luft and Ingham (1955), who developed the concept of the Johari Window. According to this concept, people have a blind area to themselves, but noticeable to others. The main objective of this research is to propose integration between the result of Belbin Test and Johari Window. To achieve this purpose Belbin Test will was applied in a defined public. The survey results confirmed that the Belbin test shows that outside observers demonstrate knowledge of observed that the same do not show